Analyzing the Multimodal Discourse of the Tenth Grade English Work in Progress Textbook - Hafiz, Alfanda; Kurniawati, Dewi; Aryanika, Septa; Verawati, Heni; Firdaus, Wihda Yanuar (Journal of Linguistics and Social Sciences, 2024)
The most widely utilized educational tool across all grade levels is the textbook. Visual images are just one of the many crucial elements in a textbook. Textbook images serve a crucial purpose to improve students' learning and comprehension as they aid in the implementation and visualization of abstract or difficult ideas. Understanding multimodality is necessary in order to understand the meaning of an image. Thus, multimodal discourse analysis (MDA) is the most suitable approach for this research because it will evaluate parts of visual image elements in full detail. The purpose of this study is to determine the characteristics of certain English textbooks are most dominant and how visual pictures might be represented using multimodal discourse. The framework for this qualitative study is multimodal discourse analysis. visual data was taken from the question sheets from chapters 1 through 6 of the English Work In Progress textbook for the tenth grade Merdeka curriculum. Kress and Van Leeuwen used visual grammar analysis to analyze visual data. The analysis conducted by the research found that every image on the question sheet matched the text provided, either as an instruction or a question. The images were made in a style that is typically used by high school students and were highly detailed. and provide information to help students develop critical and creative thinking. To help students in understanding the questions, the majority of the images are placed below the informative text. According to Kress and Van Leeuwen's theory of visual grammar analysis, in the representational mode the most dominant is the male subject or human image which accounts for 50% of the images in the textbook. In the interactive mode, the most dominant is medium shot and full color saturation with 19% and the last most dominant compositional mode is informative with 39%.